Mix & Match: Cost Me if U Can - Zamri, Norhayati; Abdul Rani, Puteri Damia Qistina; Ahmad Muhibbuddin, Nur Syafiqah Afifah; Nik Azmi, Nik Fathiah Izzati; Ahmad Muhibbuddin, Nur Syafiqah Afrina (2025)
Game-based learning has emerged as a significant educational strategy that incorporates game elements into the learning process, thereby improving student engagement, motivation, and academic performance. In contrast with traditional classroom approaches, it encourages active engagement and experiential learning via structured challenges, prompt feedback, and rewards. This study aims to create an interactive game-based learning tool, named Mix & Match: Cost Me if U Can, intended to assist students in the process of learning. Mix & Match: Cost Me if U Can is an educational tool that employs game-based learning to help students understand the fundamentals of cost accounting, particularly cost classification, through clear definitions and relatable examples. The game enhances the learning experience by incorporating images and vibrant colours that capture students’ attention and make the process more engaging. This visual appeal ensures that learners are not limited to wordby- word memorization but are also stimulated by an exciting, interactive environment. The game also promotes the enhancement of problem-solving and decision-making abilities by engaging learners in goal-directed scenarios. Aimed at both accounting and non-accounting students enrolled in cost accounting courses, Mix & Match: Cost Me if U Can reflects how advancing technology can support personalized, student-centered learning aligned with the needs of 21st-century education.